Gestão de resíduos sólidos e biodigestor: abordagem extensionista - Medeiros, Gerson Araujo de [UNESP]; Caetano, Marina Madid Micheletti [UNESP]; Moraes, Felipe Goulart [UNESP]; Machado, Fernando Henrique [UNESP]; Paes, Michel Xocaira [UNESP]; Amancio, Diogo Torres [UNESP]; Ribeiro, Admilson Irio [UNESP]; Pinheiro, Lucas Tadeu [UNESP]; Ribeiro, Lucas Fernandes de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Municipal solid waste management is of considerable relevance in contemporary society. Such approach has been disseminate to the population and segments of society through environmental education programs, which must be contextualized to the realities of the actors involved. The objective of this project is to present the solid waste management strategies applied to a philanthropic institution in Sorocaba, state of São Paulo, incorporating the use of biodigestor. The project was developed by the Educandário Bezerra de Menezes, and had as key steps the diagnosis of solid waste generation; the development of a waste management plan; the development and testing of a digester for the generation of organic compounds for agricultural purposes; community outreach through environmental education activities in the community. The development of the project in all its stages, was attended by students of Environmental Engineering course from UNESP, Campus Sorocaba. The results of this project were presented at events and disseminated to about 12,000 people..

A gestão dos resíduos sólidos urbanos assume uma considerável relevância na sociedade contemporânea. Tal abordagem tem sido difundida junto a população e segmentos da sociedade por meio de programas de educação ambiental, os quais devem ser contextualizados as realidades dos atores envolvidos. O objetivo do presente projeto é apresentar as estratégias de gestão de resíduos sólidos aplicadas a uma instituição filantrópica, em Sorocaba-SP, incorporando o uso da tecnologia limpa do biodigestor. O projeto foi desenvolvido junto ao Educandário Bezerra de Menezes, e teve como etapas principais o diagnóstico da geração de resíduos sólidos; a elaboração de um plano de gestão de resíduos; o desenvolvimento e teste de um biodigestor para a geração de compostos orgânicos para fins agrícolas; extensão comunitária por meio de atividades de educação ambiental junto a comunidade. O desenvolvimento do projeto, em todas as suas etapas, teve a participação de alunos dos cursos de Engenharia Ambiental UNESP, Campus Sorocaba. Os resultados desse projeto foram apresentados em eventos e disseminados para cerca de 12.000 pessoas.
Keywords: Extension; Environment; Society; Extensão; Meio ambiente; Sociedade